MINOR FACTORS IN WORK ELEMENTS OF SMK3 IMPLEMENTATION OF PCI GIRDER ERECTION WORK BASED ON PP NO 50 OF 2012 - Prasetyo, Djoko; Wateno Oetomo; Sajiyo (Asosiasi Dosen Muda Indonesia, 2023)
Proving that the implementation of the Occupational Safety and Health Management System (SMK3) can be a reference that regulates various activities therein, as well as managing K3 systematically and comprehensively in a complete management system as an effort to prevent work accidents. The SMK3 assessment on the Probolinggo Banyuwangi Toll Road Development Project Package 1 aims to find out how much level of SMK3 implementation is being implemented, what factors influence the fulfillment of SMK3 implementation and then provide a response as an effort to take corrective action/improvement. Based on the results of the audit and analysis consisting of 166 criteria (Advanced Level) assessment as stated in Government Regulation No. 50 of 2012 concerning SMK3, it is known that the number of criteria fulfilled/appropriate is 149 criteria with an application percentage value of 89.76% and there are 17 The criteria are not met/not appropriate, namely with a percentage value of 10.24% (Minor Category). These results are included in the implementation assessment level category (Satisfactory). The implementation of SMK3 in the Probolinggo Banyuwangi Package 1 Toll Road Construction project is in accordance with and refers to applicable laws and regulations.